Chodatodesmus australis sp. nov. (Scenedesmaceae, Chlorophyta) from Antarctica, with the emended description of the genus Chodatodesmus, and circumscription of Flechtneria rotunda gen. et sp. nov. Issue 6 (16th November 2015) - Sciuto, Katia; Lewis, Louise A.; Verleyen, Elie; Moro, Isabella; La Rocca, Nicoletta
Abstract : The family Scenedesmaceae is a taxonomically complicated group due to its simple morphology, high phenotypic plasticity, and the presence of cryptic taxa. Over the years several taxonomic revisions, based on molecular data, affected the family. Here, we describe a new scenedesmacean species from Antarctica, Chodatodesmus australis, based on phylogenetic analyses of data from nuclear (ITS2 spacer, 18S rDNA), and plastid ( rbc L, tuf A) markers. Morphological (LM and SEM) and ultrastructural (TEM) observations, carried out both on the holotype of C. australis and on the generitype of Chodatodesmus, allow us to emend the original generic description of this genus. Our molecular and phylogenetic data also reveal the existence of a new monotypic genus, Flechtneria, inside the family Scenedesmaceae and lead to the taxonomic reassignment of some microalgal strains available in International Culture Collections to new taxa. Of the considered genomic regions, the tuf A gene was the easiest to amplify and sequence and it showed the highest phylogenetic signal, even if the number of sequences already available for this marker in the public databases was considerably lower than for the other chosen loci . The rbc L gene also provided good phylogenetic signal, but its amplification and sequencing were generally more problematic. The nuclear markers gave lower phylogenetic signals, but the 18S rDNA allowed distinction at the genus level and the ITS2 spacer had the advantage that secondary structures could be considered in the analyses. The use of more than one molecular locus is suggested to obtain reliable results in the characterization of scenedesmacean strains.